Superação de dormência em Adenanthera pavonina L - Silva Filho, Pedro (Brasil, 2024)
The Adenanthera pavonina L has a wide range of applications, particularly in urban afforestation due to its tree-like stature that readily adapts to various edaphoclimatic conditions. Its seeds find utility in jewelry making, such as earrings, necklaces, and bracelets, while its wood serves as a versatile raw material for crafts and construction. Additionally, it is explored as a phytopharmaceutical owing to its medicinal properties. However, the seed dormancy extends the time required for the establishment of uniform seedlings. This study addressed the seed dormancy of Adenanthera pavonina L through various treatments. The experiment was conducted at the Phytosanitary Laboratory of the Institute of Education, Agriculture, and Environment, at the Federal University of Amazonas (UFAM), Vale do Rio Madeira campus. Using a completely randomized design (CRD) in a 4x5 factorial arrangement, four treatments with five replications each were applied (mechanical scarification with sandpaper, mechanical scarification with sand, immersion in H2SO4 for 2 minutes, and control). Parameters such as germination (%), germination speed index, germination speed (in days), and germination speed coefficient were assessed for each treatment. Germination tests (with 5 replications of 50 seeds each) and vigor tests (with 4 treatments of 128 seeds each) considered germinated seeds, non-germinated seeds, and seeds with fungi. The results indicated that mechanical abrasion with sandpaper was the most effective treatment for overcoming the seed dormancy of Adenanthera pavonina L, while the use of H2SO4 proved more susceptible to fungal incidence. The control treatment and mechanical scarification with sand exhibited similar outcomes in terms of non-germinated seeds and low fungal incidence in both vigor and germination tests.